2007
DOI: 10.1021/es062417w
|View full text |Cite
|
Sign up to set email alerts
|

Carbon in Black Crusts from the Tower of London

Abstract: This paper investigates the origin, fluxes, and transformation of carbon compounds within black crusts on the stone walls of the Tower of London. The crusts were analyzed for elemental and organic carbon, including the water soluble fraction. Elemental carbon and low solubility compounds such as oxalates appeared to be conserved because of long residence times. Conversely, more soluble ions, like chloride and formate would be removed from the layers relatively quickly by rainfall. At higher organic carbon conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Gases and particulate matter (PM) emitted by vehicles can greatly affect ambient air quality and have direct implications for human health [1], climate change [2], visibility [3], ecosystem productivity [4], and artistic and historic buildings preservation [5], all with consequences for society and national safety and security. Pollutants emitted by vehicles are typically regulated by government agencies OPEN ACCESS (e.g., the US Environmental Protection Agency in the USA) and typically include: carbon monoxide (CO) and hydrocarbons (HC) (emitted during fuel-rich combustion conditions), nitrogen oxides (NO) (emitted during high-temperature combustion conditions), and PM.…”
Section: Introductionmentioning
confidence: 99%
“…Gases and particulate matter (PM) emitted by vehicles can greatly affect ambient air quality and have direct implications for human health [1], climate change [2], visibility [3], ecosystem productivity [4], and artistic and historic buildings preservation [5], all with consequences for society and national safety and security. Pollutants emitted by vehicles are typically regulated by government agencies OPEN ACCESS (e.g., the US Environmental Protection Agency in the USA) and typically include: carbon monoxide (CO) and hydrocarbons (HC) (emitted during fuel-rich combustion conditions), nitrogen oxides (NO) (emitted during high-temperature combustion conditions), and PM.…”
Section: Introductionmentioning
confidence: 99%
“…Here we found that more modern crusts have higher organic-carbon/sulfur (OC/SO 4 ) ratios (28). Figure 5 shows measu- …”
Section: Amarilleamientomentioning
confidence: 68%
“…The analysis of the data hinted that asymptotic lightness (L ∞ *) varied from 75-80% in remote areas (EC <1µg m-3), 60-70% at urban background sites (EC 2-3 µg m -3 ), The blackening is also related to the surface concentration of EC on buildings. Our research at the Tower of London (28) shows that the lightness (L*) of black crusts measured colorimetrically falls rapidly with EC at low concentrations, and exponentially reaches a limiting value at high concentrations ( Figure 3). The figure also suggests a minimum value of lightness L* around 35 where the EC area concentration in the crust is around 10 g m -2 and above.…”
Section: Blackening Trendsmentioning
confidence: 77%
“…After these anomalous initial results, a visual inspection on the spots where these tests were implemented shown that the stones have an impermeable surface covering. The formation of a dirtiness layer created on the stone surface by atmospheric pollution or growth of biological agents that induces stone degradation has been reported by several authors (Bonazza et al, 2007;Brimblecombe, 2000;Zappia et al, 1998;Turkington et al, 1997;Amoroso and Fassina., 1983).…”
Section: In Situ Water Absorption Capacitymentioning
confidence: 86%